EDUCATIVE HYBRID INTERVENTION AS A STRATEGY FOR REINTEGRATION TO THE CLINICAL COURSES OF UNDERGRADUATE STUDENTS DURING COVID-19 PANDEMIC (Proceedings of the International Conference on Education, 2021)
The SARS-COV-2, pandemic generated the need to modify the current clinical educational model with the challenge of promoting safety as well as the continuity of clinical education through the use of virtual platforms. Since clinical training in hospital institutions cannot be substituted, a strategic training plan was developed to guarantee protection, safety, and academic continuity for students upon their return to clinical clerkships. The objective of this project was to develop and evaluate the impact of a hybrid massive training plan as an educative strategy to give the theoretical and practical knowledge required for the safe return of undergraduate students to their respective clinical activities in the context of this pandemic. An academic program was designed through a massive hybrid strategy to train 616 undergraduate students studying clinical cycles by presential, virtual, synchronous, and asynchronous activities. To know the impact of the program, a pre-experimental study with pre-test and post-test was carried out to evaluate the acquisition of the important knowledge and skills of the program. A significant difference was found between the means of the initial and final evaluations (p
Keywords: COVID-19 Hybrid education, Clinical clerkships, Training, Distance learning, Educational model